2013
DOI: 10.1021/ac402607p
|View full text |Cite
|
Sign up to set email alerts
|

Particle Deflection in a Poly(dimethylsiloxane) Microchannel Using a Propagating Surface Acoustic Wave: Size and Frequency Dependence

Abstract: We study the effect of a propagating surface acoustic wave (PSAW) with different frequencies on particles with different sizes in microfluidic channels. We find that the deflection critically depends on the applied frequency as well as on the particle size. For fixed frequencies, large particles are deflected and migrate perpendicular to the flow direction while smaller particles only follow the streamlines of the flow field. However, with increasing frequency of the PSAW above a size dependent limit, small pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
114
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(117 citation statements)
references
References 38 publications
1
114
0
Order By: Relevance
“…It has been observed that a transition in particles' response occurs at k y 1 for most particle materials suspended in water. 3,29,30 However, the actual value can vary slightly with changes in uid composition and particle materials.…”
Section: Working Mechanismmentioning
confidence: 99%
“…It has been observed that a transition in particles' response occurs at k y 1 for most particle materials suspended in water. 3,29,30 However, the actual value can vary slightly with changes in uid composition and particle materials.…”
Section: Working Mechanismmentioning
confidence: 99%
“…On the other hand, TSAWs have been used in cross‐type acoustic particle separators to laterally migrate particles and realize separation across the microchannel width or within a sessile droplet, because particles predominantly migrate within the horizontal plane 11, 25, 26, 27. Most SAW‐based acoustofluidic separation techniques utilize forces that act on micro‐objects suspended in a horizontal plane while pushing them laterally inside the microchannel 28, 29, 30, 31, 32. The interaction between TSAWs and the fluid results in leaky acoustic waves that radiate at an angle of ≈22° (in systems comprising water and a lithium niobate (LiNbO 3 ) substrate) inside the microfluidic channel, such that the vertical component ( F v ) of the acoustic radiation force (ARF) acting on the suspended particles is ≈2.5 times greater than the horizontal component of the force ( F h ), i.e., F v ≅ 2.5 F h 33.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between TSAWs and the fluid results in leaky acoustic waves that radiate at an angle of ≈22° (in systems comprising water and a lithium niobate (LiNbO 3 ) substrate) inside the microfluidic channel, such that the vertical component ( F v ) of the acoustic radiation force (ARF) acting on the suspended particles is ≈2.5 times greater than the horizontal component of the force ( F h ), i.e., F v ≅ 2.5 F h 33. The SAW‐based acoustofluidic devices that utilize the horizontal component of an ARF are composed of an interdigitated transducer (IDT) integrated into the side of a single‐layered PDMS microchannel 30, 34, 35, 36. (see Figure S1a in the Supporting Information).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acoustic radiation forces are widely used at the MEMS (Micro Electro Mechanical Systems) scale to manipulate particles. [9][10][11] Typically, the fluid channels are on the order of half a wavelength and the radiation force on the particles is used to cause particle deflections. These systems operate at low flow rates (µL/min) and are not directly scalable to high flow rates.…”
Section: Introductionmentioning
confidence: 99%